2022
DOI: 10.51212/jdp.v15i3.152
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Implementasi Manajemen Mutu Di Sekolah Menengah Teologi Kristen

Abstract: The purpose of this study is to describe how the implementation of quality management in Pelita Nauli Middle Tapanuli High School. The research used descriptive qualitative with data collection techniques carried out by interviews, observation and documentation. The indicators developed are how to implement quality management starting from the planning stage which includes the formulation of the school's vision, mission, goals and work plans. The next stage is the implementation of each program and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…According to the National Accreditation Board of School/Madrasah (BAN S/M) (2023), there were 143 Christian religious secondary schools in Indonesia; however, only three have been accredited with a ranking of A. In addition, a study conducted by Gultom et al (2022) at a Christian religious school in the Province of North Sumatra found poor quality. The poor performance of Christian religious education is inseparable from school principals' lack of competence, particularly in leadership.…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Accreditation Board of School/Madrasah (BAN S/M) (2023), there were 143 Christian religious secondary schools in Indonesia; however, only three have been accredited with a ranking of A. In addition, a study conducted by Gultom et al (2022) at a Christian religious school in the Province of North Sumatra found poor quality. The poor performance of Christian religious education is inseparable from school principals' lack of competence, particularly in leadership.…”
Section: Introductionmentioning
confidence: 99%